Mathematics of Program Construction 9th International Conference, MPC 2008 Marseille, France, July 15-18, 2008 Proceedings - Audebaud, Philippe; Paulin-Mohring, Christine (Theoretical Computer Science and General Issues,, 2008)
This book constitutes the refereed proceedings of the 9th International Conference on Mathematics of Program Construction, MPC 2008, held in Marseille, France in July 2008. The 18 revised full papers presented together with 1 invited talk were carefully reviewed and selected from 41 submissions. Issues addressed range from algorithmics to support for program construction in programming languages and systems. Topics of special interest are type systems, program analysis and transformation, programming language semantics, program logics.